Management of primary bladder tumors at the University Clinic of Urology in Skopje in 2010 during one-year follow up. - Saidi, Skender; Georgiev, V; Popov, Z; Penev, M; Stankov, Oliver; Dohcev Sasho; Stavridis, Sotir; Ivanovski, Ognen; Saidi, M; Janevska, Vesna; Petrushevska, Gordana; Spasovska, L; et al. (My University, 2016)
Objective: The purpose of this study is to present the major clinical, pathological and outcome monitoring data from patients treated for urinary bladder cancer (UBC)during one-year follow-up. Methods: A total of 151 patients with primary bladder cancer were treated from 1 December 2010 to 30 November 2011 at University Clinic of Urology in Skopje. Histopathologicaly, 146 urothelial, 3 squamous, one adenocarcinoma and one metastatic cancer was confirmed. All patients were evaluated preoperatively by routine laboratory, urinoculture, ultrasonography and cystoscopy. Transurethral resection (TUR) was applied as a golden method for diagnostics and surgical treatment. Postoperative cystoscopy was performed in all patients at 3, 6, 9 and 12 months and the specimens were examined for progression (pathological grade and stage). The study was conducted on the 129 patients with urothelial UBC with pT1 or lower at the time of diagnosis, divided into two groups: first (n=123) treated by primary TUR alone and second group (n=6) treated by TUR and adjuvant chemo/immunotherapy. Seventeen patients with pT2 were treated by radical cystectomy with urine derivation. Results: The median patient age was 65 years (35-89). Urothelial carcinoma was confirmed in 146 (96.7%) and other carcinomas in 5 (3.3%) patients. Statistical analysis showed a significant correlation of pathological stage with the grade of malignancy (p<0.01). Recidivism, as well as grade and/or stage progression was observed in the group treated by TUR only. In the group of patients treated with TUR and chemo/immunotherapy, only grade, but not stage progression or recidivism was recorded. Conclusion: The application of EAU guidelines for bladder tumors contribute to the reduction of recidivism rate and progression of the disease.
Keywords: urinary bladder cancer; urothelial; Trans-Urethral Resection; EAU guidelines